MANAGEMENT KURIKULUM DALAM MEWUJUDKAN PENDIDIKAN HOLISTIK DI PONDOK PESANTREN : MANAGEMENT KURIKULUM DALAM MEWUJUDKAN PENDIDIKAN HOLISTIK DI PONDOK PESANTREN - Badrus shalih; Muhamad Rifan Dainuri (Jurnal Cendekia Ihya, 2026)
Abstract Contemporary education increasingly recognizes that learning outcomes cannot be limited to cognitive and academic achievement alone. This awareness has led to renewed interest in holistic education, which emphasizes the integrated development of intellectual, spiritual, emotional, and social dimensions of learners. In Islamic education, such a holistic orientation is normatively well established; however, its practical realization largely depends on how curriculum is designed and managed. This study examines the role of curriculum management in fostering holistic education within Islamic boarding schools (pesantren). Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, curriculum managers, teachers, and students. The findings reveal that curriculum management functions as a key driver of holistic education rather than merely an administrative mechanism. Curriculum planning aligned with institutional values, integrated implementation across academic and non-academic activities, and value-based evaluation practices enable the simultaneous development of students’ spiritual, intellectual, emotional, and social capacities. The study further demonstrates that holistic educational outcomes emerge from the integration of formal curriculum, religious practices, and communal life within the boarding school environment. Theoretically, this research contributes to the literature on Islamic educational management by proposing an integrative framework linking curriculum management and holistic education. Practically, the findings offer insights for Islamic educational institutions and policymakers seeking to design curricula that balance academic demands with character formation and social responsibility. Keywords:Curriculum management; Holistic education; Islamic boarding schools; Islamic education; Qualitative case study.